SOSIALISASI PENERAPAN GREEN CONSTRUCTION MANAGEMENT MELALUI PEMANFAATAN SERBUK PECAHAN AQUA SEBAGAI CAMPURAN BETON - Rambe, Muhammad Rahman; Pohan, Rizky Febriani; Wirna Arifitriana; Pulungan, Suryanti Suraja (JAMAS : Jurnal Abdi Masyarakat, 2023)
Utilizing crushed aqua powder as a concrete mix is ​​an example of Green Construction Management because it is environmentally friendly. This article was written as a result of community service activities to provide knowledge and information about the use of crushed aqua powder in construction projects carried out with Green Construction Management in Bunga Bondar Village, Sipirok District, South Tapanuli Regency, North Sumatra. Methods of delivery of activities consisted of lectures/presentations, discussions and questions and answers. After the socialization event, the success of the socialization was monitored for 2 months at the service location. The results of this activity show that more than 50% of the participants do not know/heard about the use of crushed aqua powder as a concrete mix. However, more than 50% of the participants are interested. The enthusiasm of the participants to take part in this socialization activity is very high, because almost 100% of the partners find this socialization very useful, including knowing how to sort aqua bottles around their area. The success of this activity is reflected in the very high enthusiasm of the participants. The results of monitoring for two months indicate that a follow-up plan is needed to correct deficiencies in the outreach activities.